A Post-colonial Reading of Purple Hibiscus by Chimamanda Adichie - نجمه قابلی (Naqd-i Zabān va Adabīyyāt-i Khārijī, 2016)
The present Article is a study of the effect of the indigenous cultural factors of the Igbo of Nigeria on the identity of the Nigerian Igbo women in the post-independence Nigeria as represented in Adichie’s Purple Hibiscus. Post-colonial feminists like Spivak and Holloway believe that without the recognition of the specific cultural elements surrounding the Third World women it is impossible to represent the material condition of the life of the subaltern women by methodologies of Western feminism. Through ages of suppression under patriarchy and colonialism, the ‘epistemic violence’ has suppressed the voice of the subaltern woman, and Holloway believes that the texts written by the African female authors apply particular strategies that are rooted in their indigenous cultural features to create polyphonic texts that represent the spectrum of identity and the post-colonial culture of the African woman. One of these strategies is named (re)membrance by Holloway through which myth, memory, and historical events are inscribed in the narrative to create a discourse which challenges both discourses of patriarchy and colonialism. The present article studies the significance of (re)membrance in Purple Hibiscus to represent the effect of the indigenous Igbo culture in the transition of a teen-aged girl to adulthood. Adichie shows that the identity of the African woman is a spectrum of various cultural elements of pre-colonial, colonial, and post-independence periods. Key words: indigenous culture, Igbo, epistemic violence, hybridity, Third space, (re)membrance, Third World women